Ecological aspects of endemic plant populations on Klang Gates quartz ridge, a habitat island in peninsular Malaysia - Wong, K.M.; Sugumaran, M.; Lee, D.K.P.; Zahid, M.S. (Kluwer (now part of Springer), 2010)
The population characteristics of Aleisanthia rupestris (Rubiaceae), Eulalia milsumii (Poaceae) and Ilex praetermissa (Aquifoliaceae), endemic to the Klang Gates quartz ridge north-east of Kuala Lumpur, Malaysia were studied. Whereas their narrow, natural distribution within species-poor communities in drier, less fertile conditions on the ridge can be explained by the selection of adaptive traits and reduced plant competition compared to the more extensive, surrounding richer forest communities on more fertile soils, recent disturbances altering site conditions have diminished their populations. Populations were compared among various terrain and site conditions (ridge spine or rockface, exposed or sheltered) on less disturbed and very disturbed portions of the ridge. A. rupestris was scarce or absent in sites shaded by taller vegetation, probably an inability to establish in conditions associated with deeper soil development. I. praetermissa appeared specially adapted to rockfaces where unstable substrates and poor soil development may restrict competition with other plants. All three species were adversely affected to varying degrees by disturbance and altered site conditions; invasive, fast-spreading, thicket-forming, weeds in disturbed sites on gentler terrain on the ridge spine appear to be especially detrimental to A. rupestris and E. milsumii establishment. Although the larger plant size of I. praetermissa compared to the other two species could mean it is less likely to be shaded out by invading weedy species, residual adults as well as new regeneration may not adapt to changed site conditions following disturbance. Distinguishing between adaptation (of both adults and new regeneration) to changed environmental conditions following disturbance, and ability in competing for space and resources against invading weedy species, is relevant.